Astrocyte Senescence and Metabolic Changes in Response to HIV Antiretroviral Therapy Drugs - Cohen, Justin; D’Agostino, Luca; Wilson, Joel; Tuzer, Ferit; Torres, Claudio (Frontiers in Aging Neuroscience, 2017)
With the advent of highly active antiretroviral therapy (HAART) survival rates among patients infected by HIV have increased. However, even though survival has increased HIV-associated neurocognitive disorders (HAND) still persist, suggesting that HAART-drugs may play a role in the neurocognitive impairment observed in HIV-infected patients. Given previous data demonstrating that astrocyte senescence plays a role in neurocognitive disorders such as Alzheimer’s disease, we examined the role of HAART on markers of senescence in primary cultures of human astrocytes. Our results indicate treatment HAART induces cell cycle arrest, senescence-associated beta-galactosidase and the cell cycle inhibitor p21. HAART treatment is also associated with the induction of reactive oxygen species and upregulation of mitochondrial oxygen consumption. These changes in mitochondria correlate with increased glycolysis in HAART drug treated astrocytes. Taken together these results indicate that HAART drugs induce the senescence program in human astrocytes, which is associated with oxidative and metabolic changes that could play a role in the development of HAND.